Integrasi Nilai-Nilai Kearifan Lokal Melalui Pembelajaran Berdiferensiasi di Sekolah Dasar - Inayati, Ummi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Indonesia has a variety of local wisdom spread across cities and regions. Each has its own values and characteristics that distinguish one region from another. However the progress of time has brought the local wisdom values to experience challenges and opportunities. The effort that can be made to maintain these local wisdom values remain sustainable is through integration in differential learning, especially in the elementary school level. This research is descriptive study that used a library research approach to examines various sources and relevant literature. The result of this study is to carry out the process of integrating wisdom values in the elementary schools learning practice through several steps, which are planning, identifying the readiness, determining the themes and time allocation for compiling teaching materials or modules, and developing the assessments. Furthermore the implementation of differential learning can be performed by accommodating four aspects, namely content, process, product and learning environment of students by paying attention to three domains, which are the readiness, the students' interests, and characteristics of students.Keywords: integration, local wisdom values, differential learning